Role of adenine functional groups in the recognition of the 3′-splice-site AG during the second step of pre-mRNA splicing - Gaur, Rajesh K. (The National Academy of Sciences, 2000)
The AG dinucleotide at the 3′ splice sites of metazoan nuclear pre-mRNAs plays a critical role in catalytic step II of the splicing reaction. Previous studies have shown that replacement of the guanine by adenine in the AG (AG → GG) inhibits this step. We find that the second step was even more severely inhibited by cytosine (AG → CG) or uracil (AG → UG) substitutions at this position. By contrast, a relatively moderate inhibition was observed with a hypoxanthine substitution (AG → HG). When adenine was replaced by a purine base (AG → PG) or by 7-deazaadenine (AG → c(7)AG), little effect on the second step was observed, suggesting that the 6-NH(2) and N(7) groups do not play a critical role in adenine recognition. Finally, replacement of adenine by 2-aminopurine (AG → 2-APG) had no effect on the second step. Taken together, our results suggest that the N(1) group of adenine functions as an essential determinant in adenine recognition during the second step of pre-mRNA splicing.